Soil Stabilization using Crumb Rubber Powder and Lime (International Journal of Innovative Research in Engineering & Management, 2022)
Karewa soils are widely spread in the  stateof Jammu and Kashmir and they have been used  assubgrade of pavement layers. Karewa soils are  usuallyclayey soils and are characterized as low bearing  capacity materials for flexible pavement layers.When such  soils cannot be replaced, its performance should be  increased by several modification techniques. The purpose  of this research is to evaluate the use of low contents of  lime and crumb rubber powder in the modification of  Karewa soil properties. In this study an effort is made to  obtain the optimum dosage of lime and crumb rubber  powder for stabilization of locally available Karewa soil.  Crumb rubber powder addition was made in the soil in the  proportion of 5% initially to 10%, and then 15% by weight  and unconfined Compressive Strength Tests and California  bearing ratio tests are conducted for cohesive soil with 3%,  4% and 5% lime with the varying rubber percentage 0%,  5%, 10% and 15% and the results were noted and  compared. The experimental investigations reveal that there  is a tremendous increase in the CBR value of the soil  treated with lime, thus leading to decreased thickness  requirements of the sub-base and base courses. With  addition of crumb rubber powder in soil, there is specific  increase in the shear parameters of soil as well as will  increase the permeability of soil.
Keywords: Karewa soil; CBR; OMC; MDD; Crumb rubber Powder